2017
DOI: 10.1371/journal.ppat.1006749
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide evolutionary dynamics of influenza B viruses on a global scale

Abstract: The global-scale epidemiology and genome-wide evolutionary dynamics of influenza B remain poorly understood compared with influenza A viruses. We compiled a spatio-temporally comprehensive dataset of influenza B viruses, comprising over 2,500 genomes sampled worldwide between 1987 and 2015, including 382 newly-sequenced genomes that fill substantial gaps in previous molecular surveillance studies. Our contributed data increase the number of available influenza B virus genomes in Europe, Africa and Central Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 62 publications
7
77
0
4
Order By: Relevance
“…Computational structural analyses showed that these were located in a major antigenic epitope [37]. These approaches include structural alignment methods [38] that can compare divergent virus proteins that exhibit little homology at the sequence level, but which share homology at the structural level.…”
Section: Parallel Evolution Beyond the Sequence Levelmentioning
confidence: 99%
“…Computational structural analyses showed that these were located in a major antigenic epitope [37]. These approaches include structural alignment methods [38] that can compare divergent virus proteins that exhibit little homology at the sequence level, but which share homology at the structural level.…”
Section: Parallel Evolution Beyond the Sequence Levelmentioning
confidence: 99%
“…Aside from IAV, there are two further human influenza virus types, influenza B virus (IBV) and influenza C virus (ICV) . Similar to IAV, influenza B viruses have eight genome segments including genes encoding HA and NA glycoproteins which, however, have evolved only two distinguishable HA lineages so far . Like IAV, IBV is regularly involved in seasonal influenza outbreaks in humans but until to date, only three cases of florid IBV infections have been detected .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Similar to IAV, influenza B viruses have eight genome segments including genes encoding HA and NA glycoproteins which, however, have evolved only two distinguishable HA lineages so far. [16][17][18] Like IAV, IBV is regularly involved in seasonal influenza outbreaks in humans but until to date, only three cases of florid IBV infections have been detected. 14,19 In Europe, serological studies from the 1960s showed the sporadic presence of antibodies against IBV in domestic pigs in Hungary.…”
Section: Introductionmentioning
confidence: 99%
“…Two main lineages (denoted as Victoria and Yamagata) are recognised based on differences in the hemagglutinin protein. It has been previously shown how these lineages evolved under different dynamics [Langat et al, 2017].…”
Section: Spatial Evolution Of Genomic Segments Of Influenza Bmentioning
confidence: 99%
“…Reassortment events and recombination patterns have been described for both the viral infections along with their dynamics of geographical transitions [Carrillo et al, 2005, Jackson et al, 2007, Dudas et al, 2014, Bedford et al, 2015. For influenza B virus we selected 122 and 120 unique genome sequences of, respectively, the Victoria (Vic) and Yamagata (Yam) lineages [Bedford et al, 2015, Langat et al, 2017, characterising five out of the eight gene segments and encoding: the polymerase basic subunits 1 and 2 (PB1 and PB2), the hemagglutinin (HA) and neuraminidase (NA) glycoproteins, and the non-structural protein 1 (NS1) [Bouvier and Palese, 2008]. For FMD we selected 74 whole-genome sequences (WGSs) characterising the O/ME-SA/Ind-2001 lineage [Bachanek-Bankowska et al, 2018], extracting separate alignments for each of the four structural (VP1 to VP4) and six non-structural (2A to 2C, and 3A to 3D) proteins, along with the leader polypeptide (Lpro) and the 5' untranslated region (5'UTR) alignments [Jackson et al, 2003].…”
Section: Phylogeographic Reconstructionmentioning
confidence: 99%